The evaluation of face-to-face learning is limited to the Indonesian language learning outcomes of class VII MTS Nur Al Zahrah Depok - Muhammad Syauqi Ghozi; Irham Ramdani; Yayan Sudrajat (PT. Lancar Media Komunikasi, 2022)
The purpose of this study was to determine the results of the evaluation of seventh grade students of MTs Nur Al Zahrah in learning Indonesian using CIPP. The method used in this research is descriptive qualitative. The results of this study indicate that the evaluation of the context of students' Indonesian learning outcomes in face-to-face learning is limited to the good category and is considered to have fulfilled all the stipulated provisions and regulations. Regarding the input in this study, it is included in the fairly good category, because the use of teacher learning resources only relies on books. The process in this research, learning Indonesian is going well. In product evaluation, student learning outcomes were reviewed based on report cards with an average of 82.6 in the cognitive domain, 81.3 in the psychomotor domain and in the affective domain as a whole quite good. Based on the results of the study, the authors conclude that it can be concluded that the limited face-to-face learning program at MTs Nur Al Zahrah during this pandemic is appropriate to continue with the procedures and rules that have been set because the learning outcomes of Indonesian class VII students are still in the good category. Keywords: Evaluation, Learning Outcomes, Limited Face-to-face Learning